National accounts digest 1980-1996 (CCS GeorgetownGY, 1997)
Provides summary values of main National Accounts aggregates in current and constant prices for the countries and for the CARICOM Region as a whole. Presents a detailed breakdown of the Gross Domestic Product by economic activity in current and constant prices for each country. Supplies the Gross Domestic Product by expenditure for each country.
DC